ANALYSIS OF MARKETING EFFICIENCY IN THE CHIP AGROINDUSTRY IN PUTOH VILLAGE PEUSANGAN SUBDISTRICT BIREUEN REGENCY - Nur Jannah Simatupang; Suryadi; Eva Wardah; Fadli; Riani (LPPM Universitas Malikussaleh - Indonesia, 2026)
This study aims to analyze the marketing efficiency of the chip agroindustry